Learning from Failure: The Paradigm of Failure as a Part of the STEM Project-Based Learning Process - Nur Wahyuni (Journal of Pedagogi, 2026)
This study examines the role of failure in STEM Project-Based Learning (PjBL) as a productive learning mechanism rather than an outcome to be avoided. In contemporary STEM education, failure is increasingly recognized as a critical component that supports deeper conceptual understanding, resilience, and the development of learner identity. However, its implementation remains inconsistent, necessitating a comprehensive synthesis of recent research. This study employs a qualitative approach using a Systematic Literature Review (SLR) method, analyzing peer-reviewed journal articles from reputable databases such as Scopus, Web of Science, and Google Scholar. Data were collected through a structured screening process based on inclusion and exclusion criteria, and analyzed using thematic and content analysis to identify key patterns related to cognitive, affective, and pedagogical dimensions of failure in STEM PjBL. The findings reveal that failure enhances higher-order thinking skills (HOTS), problem-solving abilities, and conceptual retention, while also fostering resilience and growth mindset. Structured models such as Return on Failure (RoF), Failure Analysis (FA), and productive failure approaches are shown to be effective in optimizing learning outcomes. Nevertheless, challenges such as cognitive load, time constraints, and negative emotional responses persist. In conclusion, failure can serve as a powerful instructional strategy when supported by appropriate scaffolding and a psychologically safe learning environment.